Modeling the spatial distribution of rainfall-induced landslide susceptibility in Infanta, Quezon, Philippines. - Abucay, E. R. (Compendium of Human Ecology Researches in the Philippines, 2003)
This study was conducted to model the spatial distribution of rainfall-induced landslide susceptibilities in Infanta, Quezon utilizing Geographic Information System (GIS). Barangay Magsaysay (upland) of Infanta, Quezon was susceptible to landslide attributed to the geotechnical properties of the soil e.g. deep clay soil with low to moderate expansion potential (PI = 16.53-33.04) and drastic change in land use in a span of six years (e.g. 52.27% reduction in forest cover, 97% increase in areas planted to annual crops). Furthermore, the model generated spatial LSI map shows that as rainfall approaches the threshold level of 150 mm, highly susceptible (LSI < 0.7) areas increase in area. This suggests that variability in rainfall amount such as those brought by high intense rainfall typhoon events could trigger landslide or mass movement in the study area.